Determination of Social Media Usage and Desire to Be Liked Levels of Kastamonu University Tourism Faculty Students - ERDOĞAN, Yakup; AYDOĞDU, Aydoğan (Kastamonu University, 2021)
This study aims to determine the social media usage and desire to be liked of Kastamonu University Faculty of Tourism students. For this purpose, a research was carried out for students studying at Kastamonu University Faculty of Tourism in the 2020-2021 academic year. The "Desire to Be Liked" scale developed by Kaşıkara and Doğan (2017) was used to determine the students' desire to be liked. The internal consistency coefficient of the 9-item scale was calculated as 0.813. The universe of the study consists of 792 students. The convenience sampling method, one of the non-probability sampling methods, was used as the sampling method. In this context, 268 students participated in the study and formed the sample. Explanatory factor analysis was applied to determine the validity and reliability of the scale with the data collected in 5-point Likert type with SPSS statistics program. To test the hypothesis, one-way ANOVA and Pearson correlation analysis were performed. In addition, frequency analysis was applied in order to obtain statistical data on demographic characteristics. As a result of the analysis, it was determined that the desire to be liked of the participants differed according to the social media networks used and the purpose of use. In addition, it was determined that there is a positive, significant and high relationship between the levels of desire to be liked and the participants' definition of social media use as addiction.
Keywords: 4. Education; 11. Sustainability; 8. Economic growth; 16. Peace & justice; 12. Responsible consumption